Some crack problem in train rails due to cylic contact loading - Lim, Xue Ting (2018)
In the railway industry, fatigue crack growth is one of the most common failure found. This may lead to accident when the train move along the rails. Therefore, fatigue life prediction is an important factor in ensuring the structural reliability in railway tracks. Currently, there are a lot of studies that was undergo regarding the fatigue crack growth of rails, however, fatigue study on cracks subjected to cyclic loading is not as common. Since a full-scale fatigue experiment cannot be carried out on railway tracks, the author has to make use of the extended finite element method (XFEM) for numerical simulations. In this project ABAQUS software was used to simulate the crack growth with different varying cases to find out what are the crack behavior if the different factor increases and also to find out what is the relationship between the crack propagation with the different factors by measuring the crack growth for each cycle and studying the results obtained. The factors include crack size, crack length, pressure amplitude and distance between the two cracks. The obtained results on fatigue crack propagation can be used for future rail design and fatigue crack assessment.